2009
DOI: 10.1111/j.1365-2036.2009.04049.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an intravenous proton pump inhibitor after endoscopic therapy with epinephrine injection for peptic ulcer bleeding in patients with uraemia: a case‐control study

Abstract: SUMMARY BackgroundPatients with peptic ulcer bleeding and uraemia are prone to re-bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…Similarly, a retrospective cohort study found that renal failure and liver disease are two independent prognostic factors of an unfavorable clinical course, including persistent or recurrent bleeding, required interventional therapy, and death [81] . Although most recurrent bleeding develops within 72 h [56,57] , uremic patients have a higher delayed recurrent bleeding risk for 7 to 30 d [10,82] .…”
Section: Factors Related With the Poor Control Of IV Ppis: Cyp2c19 Storymentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a retrospective cohort study found that renal failure and liver disease are two independent prognostic factors of an unfavorable clinical course, including persistent or recurrent bleeding, required interventional therapy, and death [81] . Although most recurrent bleeding develops within 72 h [56,57] , uremic patients have a higher delayed recurrent bleeding risk for 7 to 30 d [10,82] .…”
Section: Factors Related With the Poor Control Of IV Ppis: Cyp2c19 Storymentioning
confidence: 98%
“…In addition, the presence of co-morbidities and poor nutrition status such as uremia and hypoalbuminemia are also the significant indicators of a higher recurrent bleeding rate even when applying intravenous omeprazole infusion [6,10,82] . Kamada et al found that only one-third of patients with H. pylori-negative idiopathic duodenal ulcers may have acid hypersecretion [85] .…”
Section: Limits Of IV Ppis To Control Bleedingmentioning
confidence: 99%
“…In addition, ESRD is associated with lower albumin levels and poor nutrition, thereby possibly leading to slower ulcer healing and, perhaps, a greater risk of rebleeding (33). The impact of gastric acid secretion remains unclear because it has been shown to be increased in some studies, and decreased or normal in others (33,37).…”
Section: Other Biasmentioning
confidence: 99%
“…Patients with ESRD exhibit higher rates of rebleeding (up to 40.6% in study by Cheung et al [32]), as well as increased delayed rebleeding (beyond seven days) (16,33). ESRD has also been associated with increased long-term peptic ulcer rebleeding (34).…”
Section: Other Biasmentioning
confidence: 99%
See 1 more Smart Citation